Modeling technology based on fuzzy object-oriented Bayesian belief networks - Yershov, S.V.; Kostukevich, F.V. (PROBLEMS IN PROGRAMMING, 2018)
The basic components of information technology inductive modeling causation under uncertainty based on fuzzy object-oriented Bayesian networks is proposed. The technology is based on a combination of transformation algorithms Bayesian network in the junction tree. New more efficient algorithms for Bayesian network transformation are resulted from modifications known algorithms; algorithms based on the use of more information on the graphical representation of the network are considered. Structurally functional model are described, it is designed to implement the transformation of fuzzy object-oriented Bayesian networks.Problems in programming 2016; 2-3: 179-187